Iranian women entrepreneurs: Good, Bad, Ugly - Mina Fam, Zahra (Journal of Entrepreneurship, Business and Economics; Vol 10 No 2 (2022): Theme: Contemporary Issues in Business and Management, 2022)
Women, like men, have achieved many successes in the field of business. In the following, we intend to introduce Iranian women entrepreneurs. When it comes to business or entrepreneurship, women entrepreneurs can show strength on par with men due to the many successes they have achieved in this field. In today's era, we see more desire of Iranian women to participate economically, socially and especially to study for higher scientific degrees, which makes them very active in the field of entrepreneurship. Most of these women are the founders of multinational companies and have reached their maximum goals in today's world and this way continues. Our world has seen many successful leaders and women in various fields including politics, fashion, design, music, entertainment, technology and science. In this article, we are going to introduce some Iranian women entrepreneurs, Research paper Keywords: Women Entrepreneurs, Iran, Entrepreneurship, Business, Female Reference to this paper should be made as follows: Mina Fam, Z. (2022). Iranian women entrepreneurs: Good, Bad, Ugly. Journal of Entrepreneurship, Business and Economics , 10 (2), 63–85.